Minoranze e diritto ruolo e prospettive dell'opposizione in Italia - Nicotra, Ida (2022)
Law and minorities. Roles and perspectives of parliamentary opposition in Italy · As is well known, opposition party groups operating in representative democracies rely on a wide range of constitutional protections ensuring that they have a voice in lawmaking processes. It is against this background that this paper contributes to the debate with a look at Italy and its main mechanisms (be they statutory or not) to guarantee a minority-friendly distribution of power in parliament.
Keywords: Parliamentary Opposition; Minority Rights; Representative Democracies; Power Distribution